2023
DOI: 10.1007/s42452-023-05359-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemistry and fineness of metakaolin on the fresh properties and heat resistance of blended fly ash-based geopolymer

Abstract: Sensible thermal energy storage using concrete as a storage medium is a promising technology that helps minimize energy in power plant. The purpose of this study is to evaluate the potential benefits of metakaolin (MK) as a partial substitute for fly ash-based geopolymer for heat resistance. As a partial substitute (5 and 20 wt.%) for fly ash (FA), nine metakaolins containing different alumina contents were selected. In order to assess their potential for storing high-temperature thermal energy, physical and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For example, Abbass et al indicated that a high content of alumina in metakaolin enhanced the heat resistance of geopolymer materials. Moreover, it was also demonstrated that the higher the fineness of the metakaolin, the better the thermal properties of the geopolymer [81].…”
Section: Role In the Development Of Fire-resistant Materialsmentioning
confidence: 97%
“…For example, Abbass et al indicated that a high content of alumina in metakaolin enhanced the heat resistance of geopolymer materials. Moreover, it was also demonstrated that the higher the fineness of the metakaolin, the better the thermal properties of the geopolymer [81].…”
Section: Role In the Development Of Fire-resistant Materialsmentioning
confidence: 97%
“…or natural raw materials (clay, lateritic soils, volcanic ash, etc.) [11][12][13][14][15]. The stabilization mechanism in geopolymer materials can differ significantly depending on the type of heavy metals and the nature of the aluminosilicate used.…”
Section: Introductionmentioning
confidence: 99%